Students’ perceptions of the medical curriculum at the University of Limpopo - Mamashela, Thakadu Arnold (My University, 2024)
Any educational program follows a process of development by various stakeholders. Program evaluation is an important step in curriculum development and implementation. This study evaluated the medical curriculum delivery from the perspective of the students at the new medical school of the University of Limpopo. The research employed a cross-sectional descriptive quantitative method using a survey. All students registered for the medical curriculum in their second to fifth years of study were invited to participate in the research. The findings of this research showed there was a perception of factual overload in some modules, however, most of the modules were perceived to have been well taught with mixed methods of assessment strategies applied across the year levels of study. The infrastructure and the equipment required for teaching and learning activities were not considered satisfactory. Students embraced the use of technology in teaching and learning. The university provided adequate support in relation to WiFi on campus. Recommendations for teaching/ practice and future research were made.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Health Sciences Education to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Program evaluation; Medical curriculum; SDG-4: Quality education